Effect of Moisture Content on Foaming Behaviour of Poly(vinyl alcohol) During Thermal Foaming Process - Shi, H.; Wang, Q.; Li, L.; Meng, W.B. (Asian Journal of Chemistry, 2014)
A polar poly(vinyl alcohol) foam was studied as a function of water content by thermal processing method in present study. The effect of moisture on the melting behaviour of poly(vinyl alcohol) as well as the mechanism of cell nucleation and bubble growth were investigated. The results showed that the water in modified poly(vinyl alcohol) could act as plasticizer to realize the thermal processing of poly(vinyl alcohol) at the early plasticization stage and then volatilize into bubbles in poly(vinyl alcohol) matrix as the blowing agent at the subsequent foaming stage. With the increase of the initial water content, more blowing agent diffused from poly(vinyl alcohol) matrix into the cells due to the increased pressure drop (DPw), leading to the bubble expansion and the decrease of the apparent density of poly(vinyl alcohol) foam. When the initial water content was 22.7 wt % and the foaming temperature was 180 °C, poly(vinyl alcohol) foam with relatively uniform cell structure could be obtained.